Immunoglobulins in Jamaicans and Nigerians with immunogenetic typing of myeloma and lymphoma in Jamaicans - McFarlane, H. (1970)
Serum IgG concentration was lower in Jamaicans than in Nigerians. The maternalfoetal IgG ratio was also lower in Jamaican sera than in Nigerian sera. It is suggested that endemic malaria in Nigeria may be responsible for these differences. The higher IgM concentration in the Nigerian cord sera may be further evidence of this. Eighteen new cases of myeloma were detected in Jamaicans between August 1966 and May 1967. Based on Gm typing, only two of these showed evidence of mixed white ancestry. All the others had the typical Gm groups of Negroes. Similarly, only two patients out of a total of 17 with malignant lymphoma showed evidence of mixed white ancestry. Twelve of the patients with myeloma showed serum proteins of the IgG type, five were IgA, and one had only light chains in the serum. The majority of the patients had myeloma protein of the kappa type. The Gm typing suggested that six patients had myeloma protein of the γ1 heavy chain subclass, and one patient had a γ3 subclass heavy chain, the remainder belonging most likely to the γ2 heavy chain subclass since γ2 occurs about four times as frequently as γ4.